Kojic acid derivative and a method for producing the same - Mohamad, Rosfarizan; Basri, Mahiran; Salleh, Abu Bakar; Ariff, Arbakariya; Ashari, Siti Efliza (2012)
The present invention relates to a kojic acid derivative that is usable as whitening agent in cosmetic formulation. The kojic acid derivative is produced by esterification process between kojic acid and oleic acid utilizing enzyme in a solvent free system. The present invention also related to a method for producing the kojic acid derivative comprises of mixing kojic acid and oleic acid to form a mixture; stirring the mixture; adding an enzyme to the mixture; and filtering the mixture to obtain the kojic acid derivative.